IGF1 drives Wnt-induced joint damage and is a potential therapeutic target for osteoarthritis - Ana Escribano-Núñez; Frederique M. F. Cornelis; Astrid De Roover; An Sermon; Frédéric Cailotto; Rik J. Lories; Silvia Monteagudo (Nature Communications)
Abstract Osteoarthritis is the most common joint disease and a global leading cause of pain and disability. Current treatment is limited to symptom relief, yet there is no disease-modifying therapy. Its multifactorial etiology includes excessive activation of Wnt signaling, but how Wnt causes joint destruction remains poorly understood. Here, we identify that Wnt signaling promotes the transcription of insulin-like growth factor 1 (IGF1) in articular chondrocytes and that IGF1 is a major driver of Wnt-induced joint damage. Male mice with cartilage-specific Igf1 deficiency are protected from Wnt-triggered joint disease. Mechanistically, Wnt-induced IGF1 transcription depends on β-catenin and binding of Wnt transcription factor TCF4 to the IGF1 gene promoter. In a clinically relevant mouse model of post-traumatic osteoarthritis, cartilage-specific deletion of Igf1 protects against the disease in male mice. IGF1 silencing in chondrocytes from patients with osteoarthritis restores a healthy molecular profile. Our findings reveal that reducing Wnt-induced IGF1 is a potential therapeutic strategy for osteoarthritis.